Model for projections and simulations of the Brazilian economy - Eustáquio José Reis; Marco Antônio Freitas de Hollanda Cavalcanti; Alexandre Samy de Castro; José Luiz Rossi; Emerson Rildo de Araújo; Beatriz Muriel Hernández (Institute for Applied Economic Research (ipea), 2015)
This paper presents the latest version of the annual econometric model for the Brazilian economy developed by the Group of Macroeconomic Analysis and Modelling (Gamma) at IPEA/DIPES. The model is designed to make medium run projections and policy simulations. The specification of the model is basically Keynesian. Estimation features include the use of various time series methods, such as FIML (full information maximum likelihood) cointegration analysis and time varying parameters, besides OLS and instrumental variables estimation. In general, the development of the model's equations has explicitly tried to ensure desirable long-run properties as well as reasonable short-run dynamics.
Keywords: 330